Measuring mentalizing in youth: further validation of the reflective functioning questionnaire for youth (RFQY-13) - Martin-Gagnon, Gabriel; Fonagy, Peter; Bégin, Michaël; Normandin, Lina; Ensink, Karin (Frontiers in Psychology, 2023)
Objective: This study investigated the psychometric properties, including the factor structure, validity, and reliability of the 13-item Reflective Function Questionnaire for Youth (RFQY-13), using a new scoring system.: A community sample of 414 adolescents and a clinical sample of 83 adolescents (aged 12-21) completed the RFQY, the Borderline Personality Features Scale for Children (BPFS-C), the Beck Youth Inventories (BYI), the Child Behavior Checklist-Youth Self Report (CBCL-YSR) and the Movie for the Assessment of Social Cognition (MASC).Results : Using the new scoring system, our results demonstrated configural and metric invariance, as well as adequate reliability and validity across both samples for the two-factor structure of the RFQY. The Uncertainty subscale showed strong associations with psychopathology and differentiated between clinical and community samples, with the clinical sample reporting significantly higher Uncertainty.Discussion : The findings show that the RFQY-13, when used with the new coding system, has good psychometric properties and is a reliable measure of mentalizing for adolescents and young adults. We discuss clinical implications, limitations and future directions.